STUDI PEMENUHAN HAK WARGA NEGARA MENDAPATKAN PEMBANGUNAN DESA DAN PEMBERDAYAAN MASYARAKAT DESA MELALUI IMPLEMENTASI KEBIJAKAN DANA DESA DI DESA TAMBAKBOYO KABUPATEN SUKOHARJO - Subekti, Ari Sri; Gunawati, Dewi; Yuliandari, Erna (Prodi PPKn FKIP UNS, 2018)
ABSTRACTThe objective of the research was to describe the implementation and the factors influencing the implementation of the Dana Desa? policies in fulfilling the citizens' right to development of village and empowering of village society in Tambakboyo Village, Sukoharjo District. The research method is qualitative. The research approach is descriptive qualitative. The results of the research: First, implementation activities include the stage of interpretation, organizing, and application. Second, the fulfillment of the right for the community in the form of increased participation of executor, right of information, right of development and empowerment of justice, based on priority analysis, and based on village typology. Third: the factors that influence the implementation of the Interpretation of the policies; budget resources, equipment, non-physical infrastructure; social, economic, and political conditions, and inter-organizational communication. Keywords: Right, Dana Desa policies, Development of Village, Empowerment of Village Society